The Immune System and the Antiviral Responses in Chinese Giant Salamander, Andrias davidianus - Jiang, Nan; Fan, Yuding; Zhou, Yong; Meng, Yan; Liu, Wenzhi; Li, Yiqun; Xue, Mingyang; Robert, Jacques; Zeng, Lingbing (Frontiers in Immunology, 2021)
The Chinese giant salamander, belonging to an ancient amphibian lineage, is the largest amphibian existing in the world, and is also an important animal for artificial cultivation in China. However, some aspects of the innate and adaptive immune system of the Chinese giant salamander are still unknown. The Chinese giant salamander iridovirus (GSIV), a member of the Ranavirus genus (family Iridoviridae), is a prominent pathogen causing high mortality and severe economic losses in Chinese giant salamander aquaculture. As a serious threat to amphibians worldwide, the etiology of ranaviruses has been mainly studied in model organisms, such as the Ambystoma tigrinum and Xenopus. Nevertheless, the immunity to ranavirus in Chinese giant salamander is distinct from other amphibians and less known. We review the unique immune system and antiviral responses of the Chinese giant salamander, in order to establish effective management of virus disease in Chinese giant salamander artificial cultivation.